Self-Authenticity dan Keseimbangan Peran Mahasiswa dalam Dunia Digital dan Akademik - Muhammad Rizqi; Surawan Surawan; Siti Norhidayah (Lembaga Yasin AlSys, 2025)
This study aims to describe the level of self-authenticity and role balance among students in coping with academic demands and the dynamics of the digital era. Using a quantitative approach with a descriptive survey design, data were collected from 92 students of the Islamic Education (PAI) Study Program, class of 2022, at IAIN Palangka Raya through the Authenticity Scale questionnaire and a role balance scale, then analyzed descriptively. The results show an average self-authenticity score of 4.91 (SD = 0.93) and a role balance score of 4.52 (SD = 1.12) on a 1–7 scale, with the majority of respondents falling within the moderate to high category. However, around 15% of students showed low scores in role balance, indicating vulnerability to identity crises due to social pressure and the influence of digital media. These findings highlight the need to strengthen digital literacy, limit the consumption of content that promotes social comparison, and internalize civic values and self-reflection to reinforce students’ personal identity. The implication is that higher education institutions need to design interventions that support psychological well-being, foster intrinsic motivation, and promote sustainable academic achievement amid the challenges of the digital era.